Correlation and path analysis studies on yield and its component traits in greengram (Vigna radiata L.) - Jilla Divya,; Neha Thomas,; G.M. Lal,; Abhinav Dayal, (Annals of Agricultural Research, 2026)
In the present investigation, 31 mungbean genotypes were evaluated for different quantitative traits to determine relationships among yield and some yield components using direct (variability, heritability, and genetic advance) and indirect selection parameters (correlation and path coefficient analysis). Significant genetic variations were observed among the genotypes for pods/plant, days to 50% flowering, days to maturity, plant height, 100-seed weight, and seed yield/plant. The magnitude of correlation revealed that seed yield/plant had a positive and highly significant correlation with plant height, number of primary branches, number of clusters per plant, number of pods per plant, biological yield, and 100-seed weight. Path coefficient analysis indicated that 100- seed weight, number of primary branches, plant height, and pod length had the maximum direct positive effect on seed yield/plant. Consequently, based on the genetic parameter correlation and path analysis, a number of effective branches, pods/plant, and 100-seed weight should be given significant precedence while formulating a selection strategy for effective improvement of mungbean varieties.